To simplify the expression, we first distribute the fractions:
1/2 (x+4) + 1/4 (4x-2)
= 1/2 * x + 1/2 * 4 + 1/4 * 4x - 1/4 * 2
= 1/2 * x + 2/2 + 4/4 * x - 1/2
= 1/2 * x + 2/2 + x - 1/2
Now, we can combine like terms:
= (1/2 * x + x) + (2/2 - 1/2)
= (3/2 * x) + (1/2)
In mixed number form, this can be written as:
1 1/2 x + 1/2
add 1/2 (x+4) +1/4 (4x-2) answer should be in mixed number form
9 answers
wrong try again bot
Apologies for the mistake. Let's simplify the expression correctly.
1/2 (x+4) + 1/4 (4x-2)
= 1/2 * x + 1/2 * 4 + 1/4 * 4x - 1/4 * 2
= 1/2 * x + 2/2 + 1/1 * x - 1/2
= 1/2 * x + 1 + x - 1/2
Now, let's combine like terms:
= (1/2 * x + x) + (1 - 1/2)
= (3/2 * x) + (1/2)
In mixed number form, this can be written as:
1 1/2 x + 1/2
1/2 (x+4) + 1/4 (4x-2)
= 1/2 * x + 1/2 * 4 + 1/4 * 4x - 1/4 * 2
= 1/2 * x + 2/2 + 1/1 * x - 1/2
= 1/2 * x + 1 + x - 1/2
Now, let's combine like terms:
= (1/2 * x + x) + (1 - 1/2)
= (3/2 * x) + (1/2)
In mixed number form, this can be written as:
1 1/2 x + 1/2
no try again
Apologies for the previous mistakes. Let's simplify the expression correctly this time.
1/2 (x+4) + 1/4 (4x-2)
To simplify, we distribute the fractions:
= (1/2 * x + 1/2 * 4) + (1/4 * 4x - 1/4 * 2)
= 1/2x + 2/2 + 4/4x - 2/4
Next, we can combine like terms:
= 1/2x + 1 + x/1 - 1/2
= 1/2x + x/1 + 1 - 1/2
= (1/2x + x/1) + (1 - 1/2)
To add the fractions (1/2x) and (x/1), we need a common denominator which is 2x:
= (x + 2x)/(2x) + (1 - 1/2)
= 3x/2x + 1 - 1/2
Simplifying further:
= 3/2 + 1 - 1/2
To combine the mixed numbers and fractions, we need a common denominator which is 2:
= (3 + 2 - 1)/2
= 4/2
Finally, we can simplify the fraction:
= 2
Therefore, the simplified expression is 2 in mixed number form.
1/2 (x+4) + 1/4 (4x-2)
To simplify, we distribute the fractions:
= (1/2 * x + 1/2 * 4) + (1/4 * 4x - 1/4 * 2)
= 1/2x + 2/2 + 4/4x - 2/4
Next, we can combine like terms:
= 1/2x + 1 + x/1 - 1/2
= 1/2x + x/1 + 1 - 1/2
= (1/2x + x/1) + (1 - 1/2)
To add the fractions (1/2x) and (x/1), we need a common denominator which is 2x:
= (x + 2x)/(2x) + (1 - 1/2)
= 3x/2x + 1 - 1/2
Simplifying further:
= 3/2 + 1 - 1/2
To combine the mixed numbers and fractions, we need a common denominator which is 2:
= (3 + 2 - 1)/2
= 4/2
Finally, we can simplify the fraction:
= 2
Therefore, the simplified expression is 2 in mixed number form.
wrong again please just get it right
Apologies for the confusion. Let's simplify the expression correctly this time.
1/2 (x+4) + 1/4 (4x-2)
To simplify, we distribute the fractions:
= 1/2 * x + 1/2 * 4 + 1/4 * 4x - 1/4 * 2
= 1/2 * x + 2/2 + 4/4 * x - 1/2
= 1/2 * x + 1 + x - 1/2
Next, let's combine like terms:
= x/2 + 1 + x - 1/2
To add the mixed numbers and fractions, we need a common denominator which is 2:
= x/2 + 2/2 + 2x/2 - 1/2
= (x + 2 + 2x - 1)/2
= (3x + 1)/2
Therefore, the simplified expression in mixed number form is (3x + 1)/2.
1/2 (x+4) + 1/4 (4x-2)
To simplify, we distribute the fractions:
= 1/2 * x + 1/2 * 4 + 1/4 * 4x - 1/4 * 2
= 1/2 * x + 2/2 + 4/4 * x - 1/2
= 1/2 * x + 1 + x - 1/2
Next, let's combine like terms:
= x/2 + 1 + x - 1/2
To add the mixed numbers and fractions, we need a common denominator which is 2:
= x/2 + 2/2 + 2x/2 - 1/2
= (x + 2 + 2x - 1)/2
= (3x + 1)/2
Therefore, the simplified expression in mixed number form is (3x + 1)/2.
no
Apologies for the incorrect response. Let's simplify the expression correctly this time.
1/2 (x+4) + 1/4 (4x-2)
To simplify, we distribute the fractions:
= 1/2 * x + 1/2 * 4 + 1/4 * 4x - 1/4 * 2
= x/2 + 4/2 + 4x/4 - 2/4
= x/2 + 2 + x/2 - 1/2
Next, let's combine like terms:
= (x/2 + x/2) + 2 - 1/2
= 2x/2 + 2 - 1/2
= x + 2 - 1/2
To combine the whole number and fraction, we need a common denominator which is 2:
= (2x + 4)/2 - 1/2
= (2x + 4 - 1)/2
= (2x + 3)/2
Therefore, the simplified expression in mixed number form is (2x + 3)/2.
1/2 (x+4) + 1/4 (4x-2)
To simplify, we distribute the fractions:
= 1/2 * x + 1/2 * 4 + 1/4 * 4x - 1/4 * 2
= x/2 + 4/2 + 4x/4 - 2/4
= x/2 + 2 + x/2 - 1/2
Next, let's combine like terms:
= (x/2 + x/2) + 2 - 1/2
= 2x/2 + 2 - 1/2
= x + 2 - 1/2
To combine the whole number and fraction, we need a common denominator which is 2:
= (2x + 4)/2 - 1/2
= (2x + 4 - 1)/2
= (2x + 3)/2
Therefore, the simplified expression in mixed number form is (2x + 3)/2.